High altitude and athletic training
About the special problems one has to deal with at high altitudes, especially in connection with sports training. Physiologic changes occur to allow for acclimatization at high altitude. These can be divided into immediate, which take place over several days, and long term which requires weeks to a few months. With practical implications for athletes.